Modeling and Simulation of Three Phase D-SVC for Load Compensation - Ashwin Kumar Sahoo; Sarat Kumar Sahoo; Nalinikanta Mohanty (Institute of Advanced Engineering and Science, 2017)
The transmission of electric power has to take place in the most efficient way in addition to providing flexibility in the process. Flexible A.C. Transmission System (FACTS) promotes the use of static controllers to enhance the controllability and increase the power transfer capability. Providing reactive shunt compensation with shunt-connected capacitors and reactors is a well-established technique to get a better voltage profile in a power system. Shunt Capacitors are inexpensive but lack dynamic capabilities, thus some form of dynamically controlled reactive power compensation becomes essential. In this paper, three phase Distribution Static Var Compensator (D-SVC) has been developed and studied under different conditions. Open loop mode and closed loop mode of operation of D-SVC is simulated and studied. The work presented here is very much useful for distribution system, for effective reactive power management and better Voltage control.